KAJIAN MANFAAT KAWASAN KONSERVASI BAGI PERIKANAN YANG BERKELANJUTAN DI PESISIR TIMUR PULAU WEH - Hastuty, Riany; Adrianto, Luky; Vitner, Yon (Jurnal Teknologi Perikanan dan Kelautan, 2016)
Marine protected areas have an important effect to maintain the ecological and economical conditions. The purpose of this research was to identifed the benefits of marine proteced areas for the ecological, fisheries and stakeholders. The results showed conservation area had an average of coral cover, abundance, and biomass of reef fish is higher 54.30%, 12.147 ind/ha and 486.70 kg/ha compared to areas outside the conservation area 32.10%, 8073 ind/ha and 286.70 kg/ha. The average catches increased from the 2008 amounted to 3.03 kg/trip and in 2013 of 3.60 kg/trip. Multi-objective analysis showed that the benefits of conservation areas most perceived by stakeholders is the number of fish that more (biomass), the increase in the number of tourists and management is done with the local wisdom (hukum adat). It was concluded that the conservation area on the east coast of the Weh Island could maintain ecosystems and fish stocks properly but need improvement the quality of livelihood to improve the economic conditions.